Design and implementation of a static battery charging station for an electric vehicle. (7th June 2023) - Dwivedi, Manish Kumar; Jayapragash, R.; Kumar, N. Senthil
This paper presents an efficient hybrid battery charger (HBC) for an electric vehicle (EV). The HBC incorporated with maximum power point tracking (MPPT) algorithm receives input from the PV panels to charge the batteries when the solar insolation levels are high and is shifted to the grid at times of reduced insolation level. The HBC is implemented using two topologies. A multi-stage charger (MSC) consisting of a boost and buck converter integrated together and a single-stage charger (SSC) consisting of single-ended primary-inductor converter (SEPIC). Both the topologies are simulated in MATLAB/Simulink environment and compared. The MPPT algorithm is applied and the charge control algorithm is devised and applied for HBC. Finally, a scaled down 250W SSC is implemented in a hardware model. A modified perturb and observe (MP&O) MPPT is applied that would reduce the time complexity of the algorithm and would be more efficient.